A Retrospective Analysis of the Coagulation Dysfunction in COVID-19 Patients. (5th October 2020) - Chen, Xu; Wang, Qinghua; Xu, Min; Li, Chengbin
To discuss the coagulation dysfunction in COVID-19 patients and to find new biomarkers to separate severe COVID-19 patients from mild ones. We use a retrospective analysis of 88 COVID-19 patients, and compare the coagulation function between severe and mild groups. We found the prothrombin time (PT), thrombin time (TT), D-dimer were significantly higher in the severe group ( P < 0.05), and the highest area under the curve (AUC) is 0.91 for D-dimer, while the AUC of PT and TT were 0.80 and 0.61 respectively. We identified that D-dimer has a better value in predicting patients who are likely to develop into severe cases, with the sensitivity and specificity were 84.4% and 88.8%, respectively. D-dimer may be a good biomarker to separate the severe COVID-19 patients from the mild ones.